Nap duration and its association with hypertension-diabetes comorbidity in minority populations: evidence from the CMEC study - Zhang, Renhua; Zhou, Enhui; Liu, Leilei; Wang, Yuan; Xiao, Fei; Hong, Feng (Frontiers in Endocrinology, 2025)
ObjectiveLimited information is available on the effect of nap duration and hypertension-diabetes comorbidity (HDC) in minority people. We aimed to explore the relationship between nap duration and HDC for the co-management of hypertension and diabetes mellitus in the minority.MethodsA total of 16,911 participants from the China Multi-Ethnic Cohort (CMEC) were enrolled in this cross-sectional study. Nap duration was then categorized into four groups: 0 hours (reference group), 0–0.5 hours, 0.5–1 hour, and >1 hour. Multiple logistic regression was applied to analyze the association between nap duration and HDC. Restricted cubic splines (RCS) analysis was conducted to assess the nonlinear relationship between nap duration and the co-occurrence of HDC. Subgroup analyses were subsequently performed, stratified by sex, age, and ethnicity.ResultsAmong 16,911 participants with a median age of 51.79 years, of whom 66.00% were female. A total of 647 subjects were in the HDC group, representing a prevalence rate of 3.83% in the entire study population. Multivariate logistic regression analysis showed that, after multivariate adjustments, the odds ratios (95% CI) for HDC across the four groups (0h, 0–0.5h, 0.5–1h and > 1h) were: reference, 1.305 (1.027, 1.650), 1.254 (1.016, 1.542), 1.612 (1.261, 2.046), respectively. RCS analyses revealed distinct associations between naptime duration and HDC: no significant relationship in participants aged <45 years (P-overall=0.529); a linear positive correlation in those aged 45–60 years (P-overall=0.001); and an inverse J-shaped association peaking at 60 minutes in individuals aged >60 years (P-overall=0.026, P-nonlinearity=0.015). The subgroup analysis revealed that among >45 years, male, Dong or Miao, a longer nap duration was also associated with an increased prevalence risk of HDC.ConclusionLonger napping duration were associated with an increased risk of HDC and monitoring nap duration may aid in identifying high-risk groups.